DWV Infection in vitro Using Honey Bee Pupal Tissue - Wu, Yunfei; Yuan, Xuye; Li, Jing; Kadowaki, Tatsuhiko (Frontiers in Microbiology, 2021)
The deformed wing virus (DWV) has been best characterized among honey bee viruses; however, very little is known regarding the mechanisms of viral infection and replication due to the lack of immortalized honey bee cell lines. To solve this problem, we established an in vitro system using honey bee pupal tissue to reconstruct DWV binding and entry into the host cell, followed by translation of the RNA genome and polyprotein processing using RNA-dependent RNA polymerase (RdRP) as a marker. Using this system, the P-domain of the virion subunit VP1 was found to be essential for DWV infection, but not for binding and entry into the cell. DWV efficiently infected the head tissue derived from early but not late pupa, suggesting that undifferentiated cells are targeted for viral infection. Furthermore, we found that inhibitors of mammalian picornavirus 3C-protease, rupintrivir, and quercetin suppressed RdRP synthesis, indicating that this in vitro system is also useful for screening a compound to control viral infection. Our in vitro system may help to understand the mechanism of DWV infection in host cells.